Calculation-experimental method for determining the initial geometric parameters of rubber-cord shell of rotation - V. S. Korneyev; S. A. Korneyev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The calculation-experimental method for explicitly definition the initial distributions of the angle of inclination of the cord threads, the pitch between them, the volume fractions of cord threads and rubber in the rubber-cord composite along the rotation shell meridian is presented. A brief theory of the method developed earlier with the participation of one of the authors is set forth. The main attention is paid to the procedure of sample making, the order of measurement and mathematical processing of primary data to establish the average values of the angle of inclination and pitch of the long fiber cords at the equator of the shell. The practical application of the proposed calculation-experimental method is illustrated by the example of a rubber-cord shell of the balloon type of the model N-50. The results of the study are of interest in the design of systems for shock and vibration protection of technical objects, such as underground and mobile complexes of strategic missile launchers, aircraft electronic equipment and general-purpose vehicles